Comprehensive Analysis of the Immune Response to SARS-CoV-2 Epitopes: Unveiling Potential Targets for Vaccine Development - Huixiong Deng; Yanlei Li; Gefei Wang; Rui Li (Biology)
SARS-CoV-2 continues to be a major global health threat. In this study, we performed a comprehensive meta-analysis on the epitopes of SARS-CoV-2, revealing its immunological landscape. Furthermore, using Shannon entropy for sequence conservation analysis and structural network-based methods identified candidate epitopes that are highly conserved and evolutionarily constrained in SARS-CoV-2 and other zoonotic coronaviruses. Finally, the population coverage of T cell epitopes was analyzed. The results highlighted regions within each SARS-CoV-2 protein where the immunological activity of antibodies, CD4+, and CD8+ T cell responses was predominantly concentrated. Sequence-based correlation analysis found that epitopes recognized by B cells and CD4+ T cells showed a positive correlation with high viral variability, and these high variability regions were typically linked to robust immune responses. Conversely, epitopes recognized by CD8+ T cells exhibited a negative correlation with high variability. From a structural network degree perspective, no clear correlation was identified between B cell antibody epitopes and CD4+ T cell reactivity with the degree of residue network connectivity. However, a significant positive correlation was observed between CD8+ T cell reactivity and the degree of residue network connectivity. By integrating sequence Shannon entropy and structural network correlation analysis, we pinpointed highly conserved and evolutionarily constrained SARS-CoV-2 candidate epitopes. Furthermore, we utilized immunoinformatics to assess the conservation of SARS-CoV-2 within coronaviruses and the population coverage of these epitopes. Our analysis uncovered key immune responses linked to preventing viral infection and viral clearance, emphasized areas of interest for broad-spectrum SARS-CoV-2 vaccine development, and offered insights for future research and clinical applications.